Goal directed fluid removal with furosemide versus placebo in intensive care patients with fluid overload: A trial protocol for a randomised, blinded trial (GODIF trial). Issue 9 (9th August 2022) - Wichmann, Sine; Itenov, Theis S.; Berthelsen, Rasmus E.; Lange, Theis; Perner, Anders; Gluud, Christian; Lawson‐Smith, Pia; Nebrich, Lars; Wiis, Jørgen; Brøchner, Anne C.; Hildebrandt, Thomas; Behzadi, Meike T.; et al.
Abstract: Background: Fluid overload is a risk factor for mortality in intensive care unit (ICU) patients. Administration of loop diuretics is the predominant treatment of fluid overload, but evidence for its benefit is very uncertain when assessed in a systematic review of randomised clinical trials. The GODIF trial will assess the benefits and harms of goal directed fluid removal with furosemide versus placebo in ICU patients with fluid overload. Methods: An investigator‐initiated, international, randomised, stratified, blinded, parallel‐group trial allocating 1000 adult ICU patients with fluid overload to infusion of furosemide versus placebo. The goal is to achieve a neutral fluid balance. The primary outcome is days alive and out of hospital 90 days after randomisation. Secondary outcomes are all‐cause mortality at day 90 and 1‐year after randomisation; days alive at day 90 without life support; number of participants with one or more serious adverse events or reactions; health‐related quality of life and cognitive function at 1‐year follow‐up. A sample size of 1000 participants is required to detect an improvement of 8% in days alive and out of hospital 90 days after randomisation with a power of 90% and a risk of type 1 error of 5%. The conclusion of the trial will be based on the point estimate and 95% confidence interval; dichotomisation will not be used. ClinicalTrials.gov identifier: NCT04180397. Perspective: The GODIF trial will provide important evidence of possible benefits and harms of fluid removal with furosemide in adult ICU patients with fluid overload.